Schlafen 11 Is a Novel Target for Mucosal Regeneration in Ulcerative Colitis. (17th February 2021) - Watanabe, Sho; Nishimura, Ryu; Shirasaki, Tomoaki; Katsukura, Nobuhiro; Hibiya, Shuji; Kirimura, Susumu; Negi, Mariko; Okamoto, Ryuichi; Matsumoto, Yuka; Nakamura, Tetsuya; Watanabe, Mamoru; Tsuchiya, Kiichiro
Abstract: Background and Aims: Ulcerative colitis [UC] is a chronic inflammatory disease of the colon with an intractable course. Although the goal of UC therapy is to achieve mucosal healing, the pathogenesis of mucosal injury caused by chronic inflammation remains unknown. We therefore aim to elucidate molecular mechanisms of mucosal injury by establishing in vitro and in vivo humanised UC-mimicking models. Methods: An in vitro model using human colon organoids was established by 60 weeks of inflammatory stimulation. The key gene for mucosal injury caused by long-term inflammation was identified by microarray analysis. An in vivo model was established by xenotransplantation of organoids into mouse colonic mucosa. Results: An in vitro model demonstrated that long-term inflammation induced irrecoverable changes in organoids: inflammatory response and apoptosis with oxidative stress and suppression of cell viability. This model also mimicked organoids derived from patients with UC at the gene expression and phenotype levels. Microarray analysis revealed Schlafen11 [ SLFN11 ] was irreversibly induced by long-term inflammation. Consistently, SLFN11 was highly expressed in UC mucosa but absent in normal mucosa. The knockdown of SLFN11 [SLFN11-KD] suppressed apoptosis of intestinal epithelial cells [IECs] induced by inflammation. Moreover, SLFN11-KD improved the take rates of xenotransplantation and induced the regenerative changes of crypts observed in patients with UC in remission. Conclusions: In vitro and in vivo UC-mimicking models were uniquely established using human colonic organoids. They revealed that SLFN11 is significant for mucosal injury in UC, and demonstrated its potential as a novel target for mucosal regeneration.